Salient Features of Bio-Medical Waste Management Rules, 2016 - Sheth, Jay K (Indian Journal of Community Health, 2017)
Ministry of Environment, Forest & Climate Change, Government of India published the official notification no G.S.R. 343(E) in the government gazette, dated 28thMarch 2016. With this the new law on biomedical waste called as “Biomedical Waste Management Rules, 2016” came into force in supersession of the Bio-Medical Waste (Management and Handling) Rules, 1998. Being an inevitable and inseparable part of our health care industry, it is obligatory for us that we discuss and understand the rule, legal provision as well as its implications. Being very recent, the provisions made in the new rules are not widely known. There are various changes in the new rule. An effort is made here to explain the technical aspects of the law in simpler way, comparing it with the old rule and highlighting on the key changes. Scientific basis for some changes in the rule are also highlighted appropriately. The article is particularly written to make health professionals more aware, well informed and better prepared. The larger interest however is to help & facilitate proper implementation of the rule at all levels.